The Predictive Factors of CPR Failure After 20 Minutes of Advanced Cardiac Life Support for Non-Traumatic Out-of-Hospital Arrest Cases; a Cross-sectional Study - Thongpitak Huabbangyang; Paskorn Sritipsukho (Archives of Academic Emergency Medicine)
Introduction: In patients with out-of-hospital cardiac arrest (OHCA) who receive advanced cardiac life support (ACLS) for 20 minutes, the decision of whether to continue or terminate resuscitation at the scene is difficult and complicated. This study aimed to develop and validate a simple and reliable clinical scoring system for identifying cardiopulmonary resuscitation (CPR) failure at the scene after 20 minutes of ACLS.